The Effect of CBDC Projects on Return on Assets of Euro-Zone and Non-Zone Banks in 2020-2024 - Alviando Arangga; Eni Setyowati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the impact of the development of the Central Bank Digital Currency (CBDC) project on banking profitability performance, as measured by Return on Assets (ROA), in Eurozone and non-Eurozone countries during the 2020-2024 period. This study uses a quantitative method with a panel data regression approach, and the selected model based on the test results is the Common Effect Model (CEM). Secondary data were obtained from banks' annual financial reports, central bank publications, and official financial statistics sources. This study was tested using EViews 12. The variables tested include CBDC Proxy, Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL). The results show that CAR has a positive and significant effect on ROA, while CBDC Proxy and NPL do not significantly affect ROA. These findings indicate that capital stability plays the largest role in supporting bank profitability, while CBDC projects in the development stage have not shown a direct impact on banking performance. Furthermore, the potential for disintermediation due to CBDC has not been seen to significantly affect bank revenue structure during the study period.